FROM HUMAN-CENTERED MANAGEMENT TO ALGORITHMIC GOVERNANCE: A CONCEPTUAL REVIEW OF MANAGEMENT TRANSFORMATION IN THE ARTIFICIAL INTELLIGENCE ERA - Erlangga Rahimi; Umi Narimawati; Anita Rahmawati; Sri Isti Untari; Kristin Lukitaningrum (PT. Radja Intercontinental Publishing, 2026)
The rapid development of artificial intelligence is driving a fundamental transformation in management practices and paradigms, from a human-centered approach to algorithmic governance. This article aims to conceptually examine how this shift impacts decision-making, leadership roles, organizational governance, and ethical dimensions in the context of modern management. The research method used is a conceptual literature review by analyzing reputable international journal articles and key academic books discussing humanistic management, artificial intelligence, and algorithmic governance. The results of the study indicate that algorithmic governance offers increased efficiency, consistency, and analytical capacity for organizations, but also presents risks related to transparency, accountability, fairness, and the degradation of human considerations in decision-making. This article emphasizes that human-centered management and algorithmic governance are not mutually exclusive but can be integrated within a management framework that places humans as the ultimate supervisors and bearers of responsibility for algorithm-based decisions. The study's conclusions emphasize the importance of a responsible socio-technical and governance approach so that the use of artificial intelligence can strengthen, rather than replace, human values in management practices in the digital era.